Cost-effectiveness and comparative effectiveness of cancer risk management strategies in BRCA1/2 mutation carriers: a systematic review. (October 2018) - Petelin, Lara; Trainer, Alison; Mitchell, Gillian; Liew, Danny; James, Paul
Abstract Purpose To review the evidence for the effectiveness and cost-effectiveness of cancer risk management interventions forBRCA carriers. Methods Comparative effectiveness and cost-effectiveness analyses were identified by searching scientific and health economic databases. Eligible studies modeled the impact of a cancer risk management intervention inBRCA carriers on life expectancy (LE), cancer incidence, or quality-adjusted life years (QALYs), with or without costs. Results Twenty-six economic evaluations and eight comparative effectiveness analyses were included. Combined risk-reducing salpingo-oophorectomy and prophylactic mastectomy resulted in the greatest LE and was cost-effective in most analyses. Despite leading to increased LE and QALYs, combined mammography and breast magnetic resonance imaging (MRI) was less likely to be cost-effective than either mammography or MRI alone, particularly for women over 50 andBRCA2 carriers. Variation in patient compliance to risk management interventions was incorporated in 11/34 studies with the remaining analyses assuming 100% adherence. Conclusion Prophylactic surgery and intensive breast screening are effective and cost-effective in models ofBRCA carrier risk management. Findings were based predominantly on assuming perfect adherence to recommendations without assessment of the health-care resource use and costs related to engaging patients and maximizing compliance, meaning the real-world impact on clinical outcomes and resource use remains unclear.